Has there been a Change in the Need for Additional Funds due to Covid 19? Influencing Factors - Hermuningsih, Sri; Sari, Pristin Prima; Rahmawati, Anisya Dewi (Jurnal Analisis Bisnis Ekonomi, 2022)
The need for additional funds is very much needed in situations of increased sales and macroeconomic conditions. Covid-19 Outbreak affects the firm's financial condition. The need for additional funds can be influenced by internal financial factors such as the amount of capital intensity, spontaneous and current liabilities and retained earnings. This study aims to empirically examine the factors that influence the need for funds on the 2018-2020. Observation of the data using the 2018-2020 quarterly data study. The method used to calculate the formula for additional funding needed during crisis and non-crisis and use the SPSS IBM 20 statistical tool for multiple linear regression that examines the causal relationship of variables for additional funds. The results obtained are that there is effect of the capital intensity factor, current liabilities and retained earnings on the need for additional funds, while partially the capital intensity and retained earnings have a positive effect on the need for additional funds, but the current liability factor cannot significantly affect the need for additional funds. The results of this study contribute that quarterly data provide more detailed results in developing literature related to the need for additional funds and capital intensity and the factors that influence them more so that changes can be analyzed periodically, not annually.